"Brown‐Ring"‐Related Coordination Polymers of the Quartet‐{FeNO}7 Chromophore. Issue 13 (5th March 2020) - Monsch, Georg; In‐Iam, Areenan; Kästele, Xaver; Klüfers, Peter
Abstract : A conspicuous detail of the so‐called brown‐ring test (the analytical test on nitrate) is the reddish color of the bottom layer of concentrated sulfuric acid, which develops upon the bleeding of the brown layer into the acid. Crystals of the same color form from a solution of ferrous sulfate in concentrated sulfuric acid on saturation with gaseous nitric oxide. The structure of this H3 O[{Fe(NO)(μ4 ‐SO4 )(μ2 ‐SO4 )0.5 } n/n ] (1a ) is made up from infinite chessboard‐type layers with sulfur on the field junctions and Fe(NO) moieties below the black and above the white fields. An Fe–N–O angle of about 160° causes disorder in the tetragonal space group I 4/ mmm . A similar crystal pathology was found in the related [{Fe(MeOH)(NO)(μ4 ‐SO4 )} n/n ] (1b ) in the same crystal class. A one‐dimensional coordination polymer is formed in crystals of a third compound that comprises the Fe(NO)O5 coordination pattern, namely the brown oxalato species [{Fe(H2 O)(NO)(μ2 ‐ox)} n/n · H2 O] (2 ). A still larger NO tilt of about 156° is not obscured by disorder in the triclinic crystals of 2 . Abstract :